Pengaruh Media Puzzle Huruf untuk Meningkatkan Kemampuan Membaca Anak Disleksia - Elly Rahmawati; Muhroji Muhroji (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Dyslexia is one of the common disorders in reading education often encountered by children at the elementary education level. This study aims to determine the effect of using Letter Puzzle media in improving the reading ability of dyslexic children at Elementary School through a qualitative approach with a case study design. Data collection was conducted through observation of students' behavior when using the letter puzzle media, as well as interviews with teachers and third-grade students to obtain their perspectives on the implementation of this media. The results of data analysis showed a significant improvement in students' ability to remember and recognize letters, especially the letters 'b' and 'd', after using the letter puzzle media. The challenge of maintaining students' interest and the importance of varying images on the puzzle media were identified as crucial strategies to maintain student engagement. These findings indicate that letter puzzle media can be an effective tool in supporting dyslexic children's learning in educational settings. The implications of these findings can serve as a basis for developing more interactive learning media and more inclusive school policies to support children with dyslexia in educational and family environments.